Design and experimental study of the control system for precision seed-metering device - Jianbo, Zhai; Junfang, Xia; Yong, Zhou; Shun, Zhang (International Journal of Agricultural and Biological Engineering, 2014)
The precision seeding technique has been developed at full speed along with the continuous development of new agricultural technologies, especially those concerning cultivated patterns. The seed-metering device is the key component of a precision seeder. A ground wheel is used to drive the seed-metering device of the conventional direct seeder. However, the wheel bears high resistance and easily slips. Moreover, the adjustment of the precision seeder’s seeding rate is more difficult. In order to solve these problems, a control system which could keep the rotational speed of the seed-metering device consistent with the seeder’s working speed for the precision seed-metering device was designed. The control system includes a Hall sensor, a single chip microcomputer system, a motor control module, a stepper motor and a display. The control system used a Hall sensor to measure the seeder’s working speed and employed a single chip microcomputer system to predict the rotational speed of seed-metering device. It would then determine the relationship between the seeder’s working speed and the rotational speed of the seed metering-device according to the seeder’s working state, distance between seeds and the requirement of sowing rate. The system could effectively reduce the influence of inhomogeneous sowing caused by the ground wheel’s slipping. The system was found to be reliable by the experiment. The seeding control system could also make the speed of the seed-metering device and seeder’s uniform, improving the uniformity of the amount of seeding, and achieving the goal of design. This new design provides a platform to solve problems of the seed-metering device and the seeder. Keywords: agricultural machinery, precision seeder, seed-metering device, sensor, control system, stepper motor DOI: 10.3965/j.ijabe.20140703.002 Citation: Zhai J B, Xia J F, Zhou Y, Zhang S. Design and experimental study of the control system for precision seed-metering device. Int J Agric & Biol Eng, 2014; 7(3): 13－18.